2017
DOI: 10.1177/1403494817724951
|View full text |Cite
|
Sign up to set email alerts
|

Reported habitual intake of breakfast and selected foods in relation to overweight status among seven- to nine-year-old Swedish children

Abstract: The parental reports of children's food habits pointed at favourable eating patterns for most investigated children. Breakfast skipping, diet soft drinks and low-fat milk consumption were more frequent among OW/OB children. Longitudinal studies are needed to determine the causal relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 23 publications
3
20
3
Order By: Relevance
“…Based on the figures of the ENKid study carried out by Serrá-Majem et al [31], it is revealed that in Spain the problems of obesity and the combination of this problem with overweight are similar to the figures of this study in populations with similar characteristics [32,33]. In this sense, it should be noted that in other countries there are figures that highlight that at least a fifth of boys and similarly in girls, have varying degrees of obesity [34,35].…”
Section: Discussionsupporting
confidence: 79%
“…Based on the figures of the ENKid study carried out by Serrá-Majem et al [31], it is revealed that in Spain the problems of obesity and the combination of this problem with overweight are similar to the figures of this study in populations with similar characteristics [32,33]. In this sense, it should be noted that in other countries there are figures that highlight that at least a fifth of boys and similarly in girls, have varying degrees of obesity [34,35].…”
Section: Discussionsupporting
confidence: 79%
“…The literature search identified 239 potentially relevant articles. After reviewing the titles and abstracts and the full-length articles, 39 articles were selected for closer assessment and then included in our analysis [11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49]. The search flow-chart is represented in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
“…One of the studies included a sample of 9–15 years old, enrolled in 1985, with a follow-up of about 20 years (2004–2006) at ages 26–36 years [11]. One study included only preschool-aged children [13], 27 studies included only school-aged children and adolescents [1,11,14,15,16,17,18,19,20,21,22,23,24,26,27,28,31,32,38,39,40,41,43,44,45,46,47], and 9 studies analyzed both preschool-aged and school-aged children and adolescents [25,29,30,33,34,35,36,37,42]. Most studies recorded data about breakfast skipping by food frequency questionnaires [11,14,16,18,20,22,27,28,29,31,32,33,38,39,40,43,44,45,46,47], some on a recall-based methodology or by food diaries [13,15,21,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite breakfast consumption being associated with improved health outcomes in children and adolescents [5,[10][11][12][13][14][15][16][17][18], the International Breakfast Research Initiative reports that only one third to one half of older children (11)(12)(13)(14)(15) years of age) consume breakfast every day [19]. In addition, the prevalence of skipping breakfast has been shown to increase with age [20].…”
Section: Introductionmentioning
confidence: 99%